Heuristic evaluation of e-commerce marketplace / Maslina Abdul Aziz ... [et al.] - Abdul Aziz, Maslina; Sani, Muhammad Hafizul; Baharin, Hanif; Zambri, Suzana; Jiman, Nur Idlan; Mohd Nasir, Normaya (2022)
This paper adapts one of the most popular heuristic evaluation techniques to effectively assess the design of an e-commerce marketplace. Heuristic evaluation for the e-commerce marketplace with a detailed explanation is presented as a guideline for the e-commerce marketplace. This research involved usability evaluation that analyses the e-commerce marketplace using a set of design characteristics (usability heuristics). The process of discovering usability problems is one of the three objectives of this project. The selected set of heuristics could significantly influence the results (usability findings) of performed heuristic evaluations. Based on the evaluators' evaluation, a set of heuristics was produced. This will be used as a guideline to be applied to the design of the e-commerce marketplace called University Textbook Marketplace (UniText). The result of this research presents the heuristic evaluation for e-commerce marketplace guidelines to perform a cost-effective usability evaluation of e-commerce marketplace applications. Therefore, improving website design that is both pleasurable and meets the user's and customer's needs.